Management of Common Infections in German Primary Care: A Cross-Sectional Survey of Knowledge and Confidence among General Practitioners and Outpatient Pediatricians - Peter Konstantin Kurotschka; Elena Tiedemann; Dominik Wolf; Nicola Thier; Johannes Forster; Johannes G. Liese; Ildiko Gagyor (MDPI AG, 2021)
Outpatient antibiotic use is closely related to antimicrobial resistance and in Germany, almost 70% of antibiotic prescriptions in human health are issued by primary care physicians (PCPs). The aim of this study was to explore PCPs, namely General Practitioners' (GPs) and outpatient pediatricians' (PDs) knowledge of guideline recommendations on rational antimicrobial treatment, the determinants of confidence in treatment decisions and the perceived need for training in this topic in a large sample of PCPs from southern Germany. Out of 3753 reachable PCPs, 1311 completed the survey (overall response rate = 34.9%). Knowledge of guideline recommendations and perceived confidence in making treatment decisions were high in both GPs and PDs. The two highest rated influencing factors on prescribing decisions were reported to be guideline recommendations and own clinical experiences, hence patients' demands and expectations were judged as not influencing treatment decisions. The majority of physicians declared to have attended at least one specific training course on antibiotic use, yet almost all the participating PCPs declared to need more training on this topic. More studies are needed to explore how consultation-related and context-specific factors could influence antibiotic prescriptions in general and pediatric primary care in Germany beyond knowledge. Moreover, efforts should be undertaken to explore the training needs of PCPs in Germany, as this would serve the development of evidence-based educational interventions targeted to the improvement of antibiotic prescribing decisions rather than being focused solely on knowledge of guidelines.